2015
DOI: 10.1155/2015/278326
|View full text |Cite
|
Sign up to set email alerts
|

Application of Neutron Activation Analysis for Determination of As, Cr, Hg, and Se in Mosses in the Metropolitan Area of the Valley of Toluca, Mexico

Abstract: This research presents a study of environmental monitoring at different sampling sites from the Metropolitan Area of the Valley of Toluca (MAVT), Mexico, using mosses (Leskea angustata(Tayl.) andFabronia ciliaris(Brid.)) and soil samples. The epiphytic mosses and soils were sampled in two campaigns within two periods of the year, a rainy and dry-cold season. The selected sampling sites included urban regions (UR), transitional regions (TR), and protected natural areas (PA). The samples were analyzed by the Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Energi tersebut berupa sinar gamma yang bersifat karakteristik untuk setiap unsur, sehingga terbedakan antara satu unsur dengan unsur yang lain [12]. Selain itu sensitivitas yang tinggi dengan limit deteksi kecil (ppb) dan akurat, teknik AANI sangat cocok untuk analisis unsur kelumit dan ultra-trace metal pada analisis polutan logam berat di partikulat udara [12,16].…”
Section: Km From the Gas Disposal Chimney Resulting From Residualunclassified
“…Energi tersebut berupa sinar gamma yang bersifat karakteristik untuk setiap unsur, sehingga terbedakan antara satu unsur dengan unsur yang lain [12]. Selain itu sensitivitas yang tinggi dengan limit deteksi kecil (ppb) dan akurat, teknik AANI sangat cocok untuk analisis unsur kelumit dan ultra-trace metal pada analisis polutan logam berat di partikulat udara [12,16].…”
Section: Km From the Gas Disposal Chimney Resulting From Residualunclassified
“…After that, a lower heavy metal concentrations was found in sites 1, 4, 5, 9, and 10, with low vehicular traffic, low emission of industrial pollutants and outside the influence of the prevailing winds in the MAVT (SMA-GEM 2007b ; Machado et al 2008 ). Finally, the lowest heavy metal concentrations were found in the natural areas, (sites 8 and 11) where there is a large tree cover that reduce the influence of air pollution (Machado et al 2007 ; Mejía-Cuero et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Tollocan site is a good example, where increases in heavy metals concentration were observed. This site is located close to industrial area and it presents high vehicular traffic (Wannaz et al 2006 ; Machado et al 2007 and 2008 ; Caballero et al 2014 ; Mejía-Cuero et al 2015 ). The emissions inventory shows that 2 % of PM 10 in the MATV corresponds to toxic heavy metals (Cr, Pb, Ni and Mn), which are produced by unsealed roads and soils without vegetation (SMA-GEM 2007b , 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pulverized sample was homogenized through rotation of a V-mixer for 15 h at a speed of 15 rpm. The samples were aliquoted in 120 mL Amber bottles and then were irradiated with a dose of gamma-ray 60 Co at 25 kGy for 25 h.…”
Section: Samplingmentioning
confidence: 99%
“…In addition, Ba, Sb, and Cu are +100%, +64%, and +254% high, respectively. These elements are known to be related to fuel combustion and automotive brake wear emission [3,50,[58][59][60]; Ba is particularly used in the form of BaSO 4 , which is employed as a quantitative marker for vehicular emission [3]. A temporal variation study of airborne particulates in 2015−2016 showed that the concentrations of Zn and Ba are lower during weekends than during weekdays due to road traffic reduction; by contrast, Cu and Pb rise during weekends because of an increase in industrial emissions [58].…”
Section: Comparison Of Nist Srm 1648a Urban Pm and Kriss Urban Dust Crm Candidate: Element Composition And Source Contributionmentioning
confidence: 99%